Psychological Violence and Threats to Student Safety in American Schools and Ways to Minimize These Threats - Berezina, T.N.; Simonova, M.M.; Finogenova, T.A. (Sovremennaâ Zarubežnaâ Psihologiâ, 2025)
The article presents an analysis of contemporary research on threats to psychological well-being in US high schools. A meta-analysis of publications presented to the professional community on the portal: ResearchGate was conducted. 100 articles related to the problem of security in the US educational system were analyzed; as a result, 20 publications related directly to threats to psychological well-being were identified. The research is aimed at various categories of the population: elementary, middle, and high school students, students, children and adolescents with disabilities, representatives of minorities, educators, and parents. The threats identified are 1) violence in any form, from armed to sexual, 2) racial problems, 3) problems with ensuring the rights of minorities and the need to organize effective interaction with them, 4) professional burnout of teachers. Subjective and objective factors of ensuring psychological well-being in American schools are also highlighted. Objective factors include the peculiarities of American legislation, the presence of structures that ensure the safety of the educational environment and juvenile justice. National Association of School Psychologists. Subjective factors include the peculiarities of the country's culture, in particular, the orientation toward individualism characteristic of the American mentality. Ways to minimize these threats to the psychological well-being of students include the involvement of social workers and the active involvement of parents in ensuring psychological safety at school. A three-dimensional conceptual model for improving the safety of an educational institution's environment is described and analyzed. Aspects of the model include physical, procedural, and psychological reinforcement. В статье представлен анализ современных исследований угроз психологическому благополучию в средних школах США. Был проведен метаанализ публикаций, представленных профессиональному сообществу на портале ResearchGate. Было проанализировано 100 статей, относящихся к проблеме безопасности образовательной системы США; по итогу было выделено 20 публикаций, относящихся непосредственно к угрозам психологическому благополучию. Исследования направлены на различные категории населения: обучающихся начальной, средней, старшей школы; студентов; детей и подростков с ОВЗ; представителей меньшинств; педагогов; родителей. В качестве угроз выделяются: 1) насилие в любых формах - от вооруженного до сексуального; 2) расовые проблемы; 3) проблемы с обеспечением прав меньшинств и необходимостью организации с ними эффективного взаимодействия; 4) профессиональное выгорание педагогов. Также выделены субъективные и объективные факторы обеспечения психологического благополучия в американских школах. К объективным факторам относят: особенности американского законодательства, наличие структур, обеспечивающих безопасность образовательной среды (ювенальная юстиция, национальная ассоциация школьных психологов). К субъективным факторам относят особенности культуры страны, в частности ориентацию на индивидуализм, характерную для американского менталитета. К способам минимизации данных угроз для психологического благополучия обучающихся относятся участие социальных работников в обеспечении психологической безопасности в школе и активное привлечение родителей в обеспечение психологической безопасности в школе. Описана и проанализирована трехмерная концептуальная модель повышения безопасности среды образовательного учреждения. Аспекты модели содержат физическое, процедурное, психологическое усиление.